Partition coefficient, blood to plasma ratio, protein binding and short-term stability of 11-nor-Δ9-carboxy tetrahydrocannabinol glucuronide - Skopp, Gisela; Pötsch-Schneider, Lucia Edeltraud; Mauden, Jörg Martin; Richter, Barbara (Forensic science international, 2002)
11-Nor-Δ9-carboxy tetrahydrocannabinol glucuronide (THCCOOglu) is a major metabolite of tetrahydrocannabinol in blood. Despite its mass spectrometric identification already in 1980, further physicochemical data of THCCOOglu have not been established. Therefore, the octanol/buffer partition coefficient P and the blood to plasma ratio b/p for THCCOOglu concentrations of 100 and 500ng/ml were investigated. Protein binding of the glucuronide was established from spiked albumin solutions at a level of 250ng/ml as well as from authentic samples. The data were compared to those of 11-nor-Δ9-carboxy tetrahydrocannabinol (THCCOOH). In addition, the short-term stability of THCCOOglu in plasma at different storage temperatures was studied. Analysis was performed by LC/MS/MS. The glucuronide partition coefficient P (mean: 17.4 and 18.0 for 100 and 500ng/ml, respectively) was unexpectedly lipophilic at pH 7.4. Its blood to plasma ratios averaged 0.62 and 0.68 at 100 and 500ng/ml, respectively. THCCOOglu was highly reversibly bound to albumin (mean: 97%), and the mean fraction bound did not differ from that determined from authentic samples. THCCOOglu degraded even at a storage temperature of 4°C and THCCOOH was identified as a major decomposition product.